2018
DOI: 10.1159/000494128
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Asthma and Bronchial Hyperresponsiveness and Their Characteristics in Patients with Common Variable Immunodeficiency

Abstract: Background: Common variable immunodeficiency (CVID) is one of the most frequent primary immunodeficiencies and is characterized by disturbed immunoglobulin production and dysregulation of the immune system. Results of previous studies suggest a higher prevalence of bronchial asthma (BA) in CVID patients than in the general population. We initiated this study to evaluate lung functions and identify risk factors for BA and bronchial hyperresponsiveness (BHR) in patients with CVID. Methods: Twenty-three patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…Thus, prolonged inflammation due to allergen exposure can lead to airway remodeling and promote declining lung function. 33 , 34 , 35 , 36 , 37 In this study, we characterized the effect of smooth muscle‐specific overexpression of α7 integrin on airway inflammation and resistance using acute and chronic mouse models of allergic asthma. The effect of α7 integrin downregulation in asthmatic smooth muscle in vitro has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, prolonged inflammation due to allergen exposure can lead to airway remodeling and promote declining lung function. 33 , 34 , 35 , 36 , 37 In this study, we characterized the effect of smooth muscle‐specific overexpression of α7 integrin on airway inflammation and resistance using acute and chronic mouse models of allergic asthma. The effect of α7 integrin downregulation in asthmatic smooth muscle in vitro has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Allergic asthma is associated with leukocyte infiltration and the release of an array of cytokines and chemokines that modulate ASM phenotype. Thus, prolonged inflammation due to allergen exposure can lead to airway remodeling and promote declining lung function 33–37 . In this study, we characterized the effect of smooth muscle‐specific overexpression of α7 integrin on airway inflammation and resistance using acute and chronic mouse models of allergic asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Mukozal immünitede meydana gelen defekt inhalen alerjen duyarlılığını, bronşiyal hiperreaktiviteyi ve sonuç olarak da astım gelişimini kolaylaştırır (19). Yaygın değişken immün yetmezlikli olgularda astım patogenezi hala açık değildir, çoğunlukla intrinsik astım (non atopik) görülmektedir (20). Çeşitli çalışmalarda YDİY'li olgularda astım sıklığı %9-15 oranında bildirilmiştir (15,(21)(22)(23).…”
Section: Discussionunclassified
“…The defect that occurs in mucosal immunity facilitates inhaled allergen sensitivity, bronchial hyperreactivity, and thus development of asthma ( 19 ). The pathogenesis of asthma in patients with common variable immunodeficiency is still not clear; intrinsic asthma (non-atopic) is observed mostly ( 20 ). In different studies, the frequency of asthma has been reported to range between 9% and 15% in patients with CVID ( 15 , 21 23 ).…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 , 8 Moreover, asthma can provide clues to the diagnosis of cartilage‐hair hypoplasia (CHH), CVID, SIgAD, DOCK8 deficiency, and selective IgM deficiency (SIgMD). 9 , 10 , 11 , 12 , 13 Chronic cough and pleurisy are noticed in CVID, X‐linked agammaglobulinemia (XLA), and SIgAD. 14…”
Section: Respiratorymentioning
confidence: 99%